EURADOS intercomparison on the usage of the ICRP/ICRU adult reference computational phantoms. (July 2021) - Zankl, Maria; Eakins, Jonathan; Gómez Ros, José-María; Huet, Christelle; Jansen, Jan; Moraleda, Montserrat; Reichelt, Uwe; Struelens, Lara; Vrba, Tomas
Abstract: The European Radiation Dosimetry Group, EURADOS, has organised an intercomparison study on the usage of the ICRP/ICRU voxel reference computational phantoms together with radiation transport codes. Voluntary participants have been invited to solve specific tasks and provide solutions to the organisers before a certain deadline. The tasks to be solved are of practical interest in occupational, environmental and medical dosimetry. The aims of this training activity were to investigate if the phantoms have been correctly implemented in the radiation transport codes and to give the participants the opportunity to check their own calculations against quality-assured master solutions and improve their approach, if needed. Highlights: Intercomparison study on the usage of the ICRP/ICRU reference computational phantoms together with radiation transport codes. The tasks to be solved are of practical interest in occupational, environmental and medical dosimetry. One aim of this training activity was to investigate if the phantoms have been correctly implemented in the radiation transport codes. Participants had the opportunity to check their own calculations against quality-assured master solutions. The present intercomparison exercise demonstrated once more that such studies are beneficial to the field of computational dosimetry.